Odpowiedzi

2010-03-09T16:56:01+01:00
A) 2 *(a+b+c+d)-(3a-4b-5c+6d)
2a+2b+2c+2d-3a+4b+5c-6d=-a+6b+7c-4d=-1-12+7c-4d=-13+7c-4d
b) (-4a+4b)+7(a-36)=3a+4b-252=3-8-252=3-260=-257
dla a=1, b=-2
2010-03-09T16:59:59+01:00
A) 2 *(a+b+c+d)-(3a-4b-5c+6d)
a = 1
b = -2

2* (1 - 2 + c + d) - (3*1-4* [-2] - 5c + 6d )
2 - 4 + 2c + 2d - ( 3 + 8 - 5c + 6d )
2 - 2c + 2d - 3 - 8 + 5c - 6d
-9 + 2c - 4d

b) -4a+4b)+7(a-36)
a = 1
b = -2
-4*1 + 4* (-2) + 7*1 - 252
-4 -8 + 7 - 252 = -257
2010-03-09T17:02:22+01:00
A) 2a + 2b + 2c + 2d - 3a + 4b + 5c - 6d = (-a) + 6b + 7c - 6d

= (-1) + 6(-2) + 7c - 6d
= -1 - 12 + 7c - 6d

b) -4a+4b)+7(a-36) [a gdzie się ten nawias zaczyna?]

-(4a+4b)+7(a-36) = - 4a - 4b + 7a - 252 = -4 + 8 + 7 - 252 = -241